ОЦІНЮВАННЯ ЗНАНЬ ЗДОБУВАЧІВ ОСВІТИ ЗА ДОПОМОГОЮ ТЕСТУВАННЯ ПРИ ВИКЛАДАННІ ДИСЦИПЛІНИ «ІНЖЕНЕРНА ТА КОМП’ЮТЕРНА ГРАФІКА» (Innovative professional education, 2022)
The introduction of test control in the educational process of theinstitution of professional preliminary higher education allows to implement anindividually oriented approach in assessing the level of knowledge, which increasesthe quality of training of future specialists - masters of industrial training. Test controlincreases the level of the educational process, promotes the independent work ofstudents, gives the teacher the opportunity to check a significant volume of work andanalyze students' mastery of the studied material
Keywords: testing, test control, knowledge verification, individually oriented approach, professional pre-higher education